Radish and Spinach Seedling Production and Early Growth in Response to Struvite Use as a Phosphorus Source - Neofytou, Giannis; Chrysargyris, Antonios; Antoniou, Maria G.; Tzortzakis, Nikos G. (My University, 2024)
To sustain the increasing needs of a rapidly growing population, agriculture has relied on the use of synthetic fertilizers to intensify its production. However, the economical, environmental and health impacts associated with their use have raised significant concerns, especially given the scarcity of phosphorus. Utilizing nutrient-recovered materials like struvite can enhance circularity in agriculture and reduce its reliance on synthetic fertilizers. The objective of this study was to assess the implementation of struvite as a complete substitute to triple superphosphate, for radish and spinach seedling production and early growth, with or without supplementary fertigation. In addition, two rates of struvite were examined (0.68 and 1.37 g L−1 substrate) to evaluate its solubility. In the germination of radish, struvite had similar performance with conventional fertilization, while in spinach, the use of struvite decreased mean germination times. Both plants maintained comparable growth, chlorophyll content and antioxidant capacity when struvite was used, in comparison to conventional fertilizers. However, higher struvite rates under un-fertigated conditions significantly increased the chlorophyll b and total chlorophylls in the spinach, while phenolics and flavonoids decreased, contingent on the fertigation applications. In the radish, struvite maintained similar MDA and H2O2 levels to conventional fertilization, while decreases occurred in the spinach, with the application of ST1 under un-fertigated conditions, compared with conventional fertilization. The P and N contents of the plants were also affected, though these effects varied depending on the plant species, fertigation applications and struvite rates. This variance can be attributed to the characteristics of struvite, the plant species and the cultivation practices. The results of this study suggest that struvite can be successfully implemented in seedling production, establishing significant prospects for its commercialization and use in nurseries. © 2024 by the authors.
Keywords: nutrient recovery; peat; phosphorus; struvite; vegetable crops